-9x+13=-27

Simple and best practice solution for -9x+13=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+13=-27 equation:


Simplifying
-9x + 13 = -27

Reorder the terms:
13 + -9x = -27

Solving
13 + -9x = -27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -9x = -27 + -13

Combine like terms: 13 + -13 = 0
0 + -9x = -27 + -13
-9x = -27 + -13

Combine like terms: -27 + -13 = -40
-9x = -40

Divide each side by '-9'.
x = 4.444444444

Simplifying
x = 4.444444444

See similar equations:

| x-8=4-2(3x+5) | | 3d+8=6d-2 | | n+1=-17-10n-2+9n | | xy-zy=b-c | | -n-24=5-q | | 8x+38=3(x+1) | | xy-zy=b | | 2t^3-10t=t^2 | | 15-3x=15-3x | | 7x-6-4x=2x+6 | | 10-15x=35 | | 46-7x=12+10x | | 0.3333333333333333= | | 3xy+yx= | | 3x-4=6x-1 | | ax+bc+3=-6 | | -129=6(1-4n)-3n | | -(5w+u)+3(3u+5w)= | | 4z-5=19 | | 4x=4x+7 | | -4+5k=11 | | 3x^3+5x-8=0 | | (6-5s)(2-s)= | | 7+10r=77 | | 24+13=24+15 | | -30=2(w+5)-6w | | 2x+y-z=10 | | log[2](7x+2)=6 | | 2=f/ | | 10.5=x+5.5 | | 8+(-21)+1+(-2)+16+(-10)= | | 2.3v=82.5 |

Equations solver categories